Mathematical Communication of Students Who Have Auditorial Learning Styles in Solving Rectangular Problems - Fitri Kumala Dewi; Elis Muslimah Nuraida; Michrun Nisa Ramli (UIN Sulthan Thaha Saifuddin Jambi, Pusat Kajian Kurikulum Pengembangan Pengajaran dan Pembelajaran (Center of Curriculum Studies, Teaching and Learning Development), 2022)
Mathematical communication is an important part of mathematics learning. It is important for learners to communicate mathematical problems appropriately so that students can solve these problems. In communicating mathematical problems, students face them with different responses. Students' mathematical communication skills vary due to many factors that affect them, one of these factors is learning style.This study is of a descriptive-qualitative type and aims to describe the mathematical communication of students who have an auditorial learning style in solving rectangular problems. The instruments used consisted of learning style questionnaires adapted from the VAK Learning Styles Self-Assessment Questionnaire, problem solving tests, and interview guidelines. Tests and interviews are conducted for students who have auditory learning styles. Research data were obtained from the results of written tests and interviews that were analyzed based on visual, written, and oral mathematical communication indicators. The results of the study include, (1) SA cannot write a description on the picture in full, (2) SA is able to understand the problem by writing down the information contained in the problem and is able to solve the problem appropriately, but does not write down the formula used, (3) During the interview process SA is able to reveal images according to the problem given and is able to explain verbally the mathematical ideas used in solving the problem.